An efficient healing agent for high temperature epoxy composites based upon tetra-glycidyl diamino diphenyl methane. (November 2015) - Pingkarawat, K.; Dell'Olio, C.; Varley, R.J.; Mouritz, A.P.
Abstract: Poly(ethylene- co -methacrylic acid) (EMAA) as a thermally activated healing agent in a high performance, high temperature tetra-glycidyl methylene dianiline (TGDDM)/diethyl toluene diamine (DETDA) mendable epoxy composite is reported for the first time. Despite curing above EMAAs melting point ( T m  = 85 °C), healing occurred by incorporating a preliminary low temperature curing step of 5 h at 80 °C, prior to cure at 177 °C. Healing occurred via the pressure delivery mechanism derived from tertiary amine catalysed surface condensation reactions between EMAA and hydroxyl groups from the epoxy resin. Healing efficiencies of 36%, 55% and 105% were achieved after heating at 150 °C, 200 °C and 230 °C respectively, but decreased rapidly with continued healing. Healing at 150 °C and 200 °C revealed significant healing despite remaining in the glassy state. In addition, EMAA enhanced mode I interlaminar fracture toughness by more than 270% for both the DETDA and 4, 4-DDS networks.